Efektivitas Penggunaan Bakteri Untuk Perbaikan Kualitas Air Media Budi Daya Udang Vaname (Litopenaeus vannamei) Super Intensif - Lufisari Herdianti; Kadarwan Soewardi; Sigid Hariyadi (Jurnal Ilmu Pertanian Indonesia, 2015)
Aquaculture activities in coastal area potentially produced wastes which leads water pollution. In order to reduce pollution, the use of several bacteria is very promising. This study was aimed to determine the effectivity of commercial bacterial inocculants to reduce pollution in cultured water. Bacterial inocculant tested in this study was SN®, SB®, and the combination of both inocculants for water quality improvements in white shrimp (Litopenaeus vannamei) super intensive culture media. This study was conducting in two steps, namely (i) preliminary study and (ii) primary study. The preliminary study was aimed to determine the time required to add bacteria based on the total number of bacterial colonies. The result showed that total colonies number of media treated with addition of SN® and SB® were reached maximum within 2 days. The result of primary study showed that the combination of SN® and SB® showed best effect in maintaining water quality of the culture media. This combination are proven reduces ammonia by 96%, nitrite-N by 83%, and COD by 42%.